Antagonizing miR-7 suppresses B cell hyperresponsiveness and inhibits lupus development. Issue 109 (May 2020) - Wang, Min; Chen, Hua; Qiu, Jia; Yang, Hua-xia; Zhang, Chun-yan; Fei, Yun-yun; Zhao, Li-dan; Zhou, Jia-Xin; Wang, Li; Wu, Qing-jun; Zhou, Yang-zhong; Zhang, Wen; et al.
Abstract: Objectives: The objective of this study was to address the biological function of miR-7 in an animal model of systemic lupus erythematosus. Methods: MRL lpr/lpr lupus mice were administrated antagomiR-7 or a scramble control by tail vein for 5weeks. Three groups of animals' tissues were assessed for lupus manifestations by immunofluorescence and immunohistochemistry, and serum was examined for levels of autoantibodies and inflammatory cytokines. Splenic B cell subsets were assessed for intracellular expression of PI3K signaling by FACS. Finally, the ability of the miR-7 antagomir to regulate the expansion of T follicular helper (Tfh) cells and B cell hyperresponsiveness was further explored. Results: We found that miR-7 was up-regulated in MRL lpr/lpr lupus mice and directly targeted PTEN mRNA in B cells. Up-regulated miR-7 in MRL lpr/lpr lupus B cells was negatively correlated with PTEN expression. Notably, miR-7 antagomir treatment reduced lupus manifestations in MRL lpr/lpr lupus mice. miR-7-mediated down-regulation of PTEN/AKT signaling promoted B cell differentiation into plasmablasts/plasma cells and spontaneous germinal center (GC) formation, whereas miR-7 antagomir normalized splenic B cell subtypes. Besides suppressing the activation of B cells, miR-7 antagomir intervention also down-regulated STAT3 phosphorylation and production of IL-21 and reduced Tfh expansion. Conclusion: The above data have demonstrated the critical roles of miR-7 not only in regulating PTEN expression and also B cell and Tfh cell function in lupus-prone MRL lpr/lpr lupus mice. Furthermore, the disease manifestations in MRL lpr/lpr lupus mice are efficiently improved by miR-7 antagomir, indicating miR-7 as a potential treatment strategy in SLE. Highlights: Overexpression of miR-7 in MRLlpr/lpr mice and directly targeted PTEN mRNA in B cells. MiR-7 antagonist normalized B cell hyperresponsiveness in the lupus prone MRL lpr/lpr mouse. MiR-7 antagonist treatment inhibited the expansion of TFH in spleen. Aministration of a miR-7 antagomir in vivo effectively treated clinical features of lupus in the mice.